PENGARUH STRESS TERHADAP PRODUKTIVITAS KARYAWAN DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL MODERASI DI KOPERASI TABUNGAN NASIONAL SINGARAJA (STUDI EKONOMI PSIKOLOGI DI KOPERASI TABUNGAN NASIONAL DI SINGARAJA) - Hartawan, I Gusti Made Dharma; Patni, Luh Putri Dharma (Komunitas Manajemen Kompetitif, 2023)
The purpose of this research is to find out whether stress can affect employee productivityand whether emotional intelligence can moderate the effect of stress on employee productivity. Thisresearch approach uses a quantitative approach. The data collection technique used in this study was aquestionnaire with a measuring instrument in the form of a differential sematic scale where the selectedrespondents were all employees of the Singaraja National Savings and Loans Cooperative, namely asmany as 32 people. The data analysis technique used in this study is the structural equation model(SEM) based on Partial Least Square (PLS) version 3.0. The results of this study indicate that the effectof stress on employee work productivity shows no effect and is not significant, while emotionalintelligence is only a moderating predictor. For this reason, it is expected that all employees of theSingaraja Savings and Loans Cooperative are able to reduce stress levels by increasing emotionalintelligence to support work productivity levels at the Singaraja National Savings and LoansCooperative.